1997
DOI: 10.1359/jbmr.1997.12.7.1035
|View full text |Cite
|
Sign up to set email alerts
|

Plasmin-Mediated Proteolysis of Osteocalcin

Abstract: Plasmin cleaves osteocalcin at a site within its carboxyl end, thus creating an N-midterminal 1-43 and a short C-terminal 44 -49 peptides. The products of the cleavage were identified by matrix assisted laser desorption ionization time of flight mass spectrophotometry and by reversed phase high performance liquid chromatography followed by N-terminal sequence determination. When separated by sodium dodecyl sulfide-polyacrylamide gel electrophoresis in the presence of reducing agents, large (LF; N-midterminal) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…The C-terminal pentapeptide FYGPV and an octapeptide were found to have chemotactic activity to osteoclast precursor cells (11,58). Previous studies have shown that plasmin, which is associated with osteoblast membranes, cleaves osteocalcin at the C-terminal between residues 43 and 44, arg-arg (or lys-arg), producing two peptides comprising residues 1-43 and 44-49 (59). Figure (6B) shows the osteocalcin structure in the bone binding orientation, and it is clear that the C-terminus extends outward and would be accessible to neighboring cells as well as endogenous proteinases.…”
Section: Discussionmentioning
confidence: 91%
“…The C-terminal pentapeptide FYGPV and an octapeptide were found to have chemotactic activity to osteoclast precursor cells (11,58). Previous studies have shown that plasmin, which is associated with osteoblast membranes, cleaves osteocalcin at the C-terminal between residues 43 and 44, arg-arg (or lys-arg), producing two peptides comprising residues 1-43 and 44-49 (59). Figure (6B) shows the osteocalcin structure in the bone binding orientation, and it is clear that the C-terminus extends outward and would be accessible to neighboring cells as well as endogenous proteinases.…”
Section: Discussionmentioning
confidence: 91%
“…Plasmin can activate transforming growth factor ␤ and release insulinlike growth factor from bone matrix, which may then independently stimulate osteoblast proliferation and activity. 60,61 In vitro, plasmin can cleave osteocalcin, 62 which is a bone-specific protein important for recruitment of osteoclasts and osteoblasts. 63,64 Osteoblasts express tPA, uPA, PA inhibitor 1, and a cellular receptor for uPA.…”
Section: Discussionmentioning
confidence: 99%
“…Because bone hydroxyapatite is able to absorb only intact OC molecules but not OC fragments (40,41 ), circulating intact OC, whether released from biosynthesis in osteoblasts or derived from resorption, may traffic back to the skeleton. Circulating intact OC, which is not adsorbed to hydroxyapatite, and the largest OC fragments are likely to be degraded by proteases in the circulation or peripheral organs (11,42 ).…”
Section: Discussionmentioning
confidence: 99%